09/16/2010, 08:44 PM
a typical 1729 equation
f(z + 7 e^z) + f(z + 11 e^z) = f(z + 13 e^z)
f(z + 7 e^z) + f(z + 11 e^z) = f(z + 13 e^z)
a typical 1729 equation

09/16/2010, 08:44 PM
a typical 1729 equation
f(z + 7 e^z) + f(z + 11 e^z) = f(z + 13 e^z)
09/17/2010, 01:00 AM
I thought that 7*11*13==1001 ...
Did you mean something like.. f(z + 7 e^z) + f(z + 13 e^z) = f(z + 19 e^z) ??
09/17/2010, 08:15 PM
what is your argument Ciera ?
dont know why you multiply 7 with 11 and 13 ... regards tommy1729 
« Next Oldest  Next Newest »
